Reproductive biology and postnatal development in the tent-making bat Artibeus watsoni (Chiroptera: Phyllostomidae) - Chaverri Echandi, Gloriana (2006)
In this study we investigated the reproductive patterns and postnatal development in the tent‐making bat Artibeus watsoni. We sampled two populations in the Golfito Wildlife Refuge and Corcovado National Park, south‐western Costa Rica, from June 2003 to March 2005. Most females were pregnant during the months of January and June, and most were lactating in March and July, indicating that this species exhibits seasonal bimodal polyoestry, with the first parturition peak occurring in February–March and the second in June–July. Additionally, we observed a postpartum oestrus following the first parturition, but not after the second. Females entered oestrus again in November–December and had a gestation period of c. 3 months. A female‐biased sex ratio of neonates was observed during the second parturition period, and young were born at 32 and 56% of their mothers' body mass and length of forearm, respectively. Adult proportions in length of forearm were attained faster than adult proportions in body mass, and sustained flight was only possible after 35 days of age, when pups had achieved 100 and 80% of adult length of forearm and body mass proportions, respectively. Weaning and roosting independence occurred when young were c. 30–40 days old, and young females appeared to remain close to their place of birth, at least for their first mating period, whereas adult males were never recaptured near their birth site. In addition, sexual maturity was reached in as little as 3 months in females born during the first parturition period, whereas females born during the second birth period in June–July seemed to reach maturity at 6 months of age. Our results show that A. watsoni belongs to the faster lane of the slow–fast continuum of life‐history variation in bats, which may be attributed primarily to its roosting and feeding ecology.